THE ECONOMIC IMPACT OF SPORT TOURISM ON MSMEs IN THE YOGYAKARTA REGION TOWARDS A SPORTY LIFESTYLE (Agoge Coffee Case Study) - Insanaputra, Yanuar Sathrio (Journal of Economic Development and Village Building, 2023)
The aim of this research is to determine the economic impact of sporttourism on MSMEs in the Yogyakarta area on sporty lifestyles. In this research, qualitative research and descriptive methods will be used. This research only looks for the impact felt by gathering places or gathering points for "sport tourism" activists and wants to find other facts that support this research. Then this research will also use SWOT analysis. The research results show the impact given to MSMEs by the very massive sporting events in Jogja is very good. So it can create a new market in the development of coffee shops in Jogja. that the runners' lifestyle creates a new market in the coffee shop business line in the region, because according to this research, many runners like to run in a community, then like to gather in one place and like to chat after exercising. These habits are all part of the lifestyle carried out by runners, so if you look at it from a business aspect, they can be utilized as agoge does.